Accurate band gap determination of chemically synthesized cobalt ferrite nanoparticles using diffuse reflectance spectroscopy - Lakshmi, B.; Joe Thomas, Babitto; Gopinath, Pramod (Advanced powder technology : the international journal of the Society of Powder Technology, Japan, 2021)
[Display omitted] •Cuboidal shaped CoFe2O4 Nanoparticle powder synthesized using wet chemical synthesis technique.•High value of magnetic moment per formula unit confirms the partially inverse spinel crystal structure.•Optical properties studied through Diffuse Reflectance Spectroscopy of the nanopowder and SKM formalism.•Direct and indirect band gaps accurately determined by applying a detailed band gap estimation algorithm. Optical band gap of cuboidal Cobalt ferrite (CoF) Nanoparticles (NP), synthesized using wet chemical method, was accurately determined, by combining Diffuse Reflectance Spectroscopy (DRS) of the nanopowder, Schuster-Kubelka-Munk (SKM) formalism and the application of a detailed band gap estimation algorithm, using which absorption onsets and corresponding base line segments from the Tauc plots were precisely identified. Structural and compositional characterizations such as XRD, FE-SEM, TEM and EDX, were used to conclude that the NP exhibited cubic crystal structure with an average crystallite size of 14 nm. The values of indirect and direct band gaps were calculated to be 0.79 ± 0.01 eV and 1.5 ± 0.01 eV, respectively. The band gap shift for the nanocrystallites, from the bulk band gap, estimated using the effective mass model, came up to a value of 0.084 eV, which corresponded well to the experimentally obtained direct band gap of CoF NP. The direct and indirect band gap values were found to be well consistent with the partially inverse spinel crystal structure of the NP, emphasized using magnetization measurement.